ADAT PERNIKAHAN DI KOTA PEKALONGAN - Moch. Lukluil Maknun (IAIN Pekalongan, 2013)
This study is naturalistic research that aims to explore the marriage tradition in Pekalongan City, that has some difference’s with marriage tradition in Java. From this study, it can be revealed that the wedding stage in the city of Pekalongan in general is; nakokke, sangsangan, nentokke dino, pasrahan tukon, malem midodaren, walimah, aqad nikah, resepsi, and balik kloso. The wedding customs that distinguish Pekalongan with custom Java in general are: (1) the permissibility of dating after fiance, (2) a series of ceremonies seem quick, (3) The word 'walimah' is defined as a reading of 'mawlid al-barzanji’ before marriage contract (4) the bride and groom do not sit biting at the contract, (5) there is a term ‘bedhol gelung’, (6) there is a term ‘balik kloso sisan tilik’, (7) there is a term ‘nunggak seme’; (8) invitations related to weddings there are several kinds.